Pengaruh Literasi Digital dan Persepsi Risiko Orang Tua Terhadap Praktik Sharenting di Media Sosial - Hasanah, Rusyda Hijriyati; Rahmah, Elva (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2025)
Sharenting is a term that refers to the behavior of parents who routinely share their children's activities in visual form (photos or videos) through various social media platforms. This study aims to explore the influence of parents' digital literacy skills and risk perception on sharenting activities on social media. This study adopted a quantitative method using survey technique as the data collection instrument. By applying the snowball sampling method, 70 participants were involved in filling out the questionnaire. Data analysis was conducted by utilizing IBM SPSS Statistic software version 26.. The results of this study yielded several important findings: (1) the level of digital literacy shows a significant negative correlation with sharenting practices, indicating that an increase in parents' digital literacy ability decreases their tendency to practice sharenting; (2) risk perception has a significant positive influence on sharenting behavior, meaning that the higher parents' awareness of risk, the higher the frequency of sharenting. This reflects the phenomenon known as privacy paradox, where knowledge of potential dangers does not reduce the sharing of children's content; and (3) parents' digital literacy and risk perception simultaneously have a significant influence on sharenting practices with a total contribution of 48.8%.